A binary feedback scheme for congestion avoidance in computer networks with a connectionless network layer. - Ramakrishnan, K. K. (Computer communication review.)
We propose a scheme for congestion avoidance in networks using a connectionless protocol at the network layer. The scheme uses feedback from the network to the users of the network. The interesting challenge for the scheme is to use a minimal amount of feedback (one bit in each packet) from the network to adjust the amount of traffic allowed into the network. The servers in the network detect congestion and set a congestion indication bit on packets flowing in the forward direction. The congestion indication is communicated back to the users through the transport level acknowledgement. The scheme is distributed, adapts to the dynamic state of the network, converges to the optimal operating point, is quite simple to implement, and has low overhead while operational. The scheme also addresses a very important aspect of fairness in the service provided to the various sources utilizing the network. The scheme attempts to maintain fairness in service provided to multiple sources. This paper presents the scheme and the analysis that went into the choice of the various decision mechanisms. We also address the performance of the scheme under transient changes in the network and for pathological conditions.